A phenomenological explication of dream interpretation among rural and urban Nguni people - Schweitzer, Robert David (Rhodes University, Faculty of Humanities, Department of Psychology, 1984)
Psychologists investigating dreams in non-Western cultures have generally not considered the meanings of dreams within the unique meaning-structure of the person in his or her societal context. The majority of dream studies in African societies are no exception. Researchers approaching dreams within rural Xhosa and Zulu speaking societies have either adopted an anthropological or a psychodynamic orientation. The latter approach particularly imposes a Western perspective in the interpretation of dream material. There have been no comparable studies of dream interpretation among urban blacks participating in the African Independent Church Movement. The present study focuses on the rural Xhosa speaking people and the urban black population who speak one of the Nguni languages and identify with the African Independent Church Movement. The study is concerned with understanding the meanings of dreams within the cultural context in which they occur. The specific aims of the study are: 1. To explicate the indigenous system of dream interpretation as revealed by acknowledged dream experts. 2. To examine the commonalities and the differences between the interpretation of dreams in two groups, drawn from a rural and urban setting respectively. 3. To elaborate upon the life-world of the participants by the interpretations gained from the above investigation. One hundred dreams and interpretations are collected from two categories of participants referred to as the Rural Group and the Urban Group. The Rural Group is made up of amagqira [traditional healers] and their clients, while the Urban Group consists of prophets and members of the African Independent Churches. Each group includes acknowledged dream experts. A phenomenological methodology is adopted in explicating the data. The methodological precedure involves a number of rigorous stages of explication whereby the original data is reduced to Constituent Profiles leading to the construction of a Thematic Index File. By searching and reflecting upon the data, interpretative themes are identified. These themes are explicated to provide a rigorous description of the interpretative-reality of each group. Themes explicated within the Rural Group are: the physiognomy of the dreamer's life- world as revealed by ithongo, the interpretation of ithongo as revealed through action, the dream relationship as an anticipatory mode-of-existence, iphupha as disclosing a vulnerable mode-of-being, human bodiliness as revealed in dream interpretations and the legitimation of the interpretative-reality within the life-world. Themes explicated within the Urban Group are : the physiognomy of the dreamer's life-world revealed in their dream-existence, the interpretative-reality revealed through the enaction of dreams, tension between the newer Christian-based cosomology and the traditional cultural-based cosmology, a moral imperative, prophetic perception and human bodiliness, as revealed in dream interpretations and the legitimation of the interpretative-reality within the life-world. The essence of the interpretative-reality of both groups is very similar and is expressed in the notion of relatedness to a cosmic mode-of-being. The cosmic mode-of-being includes a numinous dimension which is expressed through divine presence in the form of ancestors, Holy Spirit or God. These notions cannot be apprehended by theoretical constructs alone but may be grasped and given form in meaning-disclosing intuitions which are expressed in the lifeworld in terms of bodiliness, revelatory knowledge, action and healing. Some differences between the two groups are evident and reveal some conflict between the monotheistic Christian cosmology and the traditional cosmology. Unique aspects of the interpetative-reality of the Urban Group are expressed in terms of difficulties in the urban social environment and the notion of a moral imperative. It is observed that cultural self-expression based upon traditional ideas continues to play a significant role in the urban environment. The apparent conflict revealed between the respective cosmologies underlies an integration of traditional meanings with Christian concepts. This finding is consistent with the literature suggesting that the African Independent Church is a syncretic movement. The life-world is based upon the immediate and vivid experience of the numinous as revealed in the dream phenomenon. The participants' approach to dreams is not based upon an explicit theory, but upon an immediate and pathic understanding of the dream phenomenon. The understanding is based upon the interpreter's concrete understanding of the life-world, which includes the possibility of cosmic integration and continuity between the personal and transpersonal realms of being. The approach is characterized as an expression of man's primordial attunement with the cosmos. The approach of the participants to dreams may not be consistent with a Western rational orientation, but nevertheless, it is a valid approach. The validity is based upon the immediate life-world of experience which is intelligible, coherent, and above all, it is meaning-giving in revealing life-possibility within the context of human existence.
Keywords: Nguni (African people) -- Religion; Nguni (African people) -- Psychology; Dreams; Dreams -- Psychological aspects; Healing -- South Africa -- Religious aspects